The coding microsatellite mutation profile of PMS2-deficient colorectal cancer - Ten Broeke, Sanne W.; Ballhausen, Alexej; Ahadova, Aysel; Suerink, Manon; Bohaumilitzky, Lena; Seidler, Florian; Morreau, Hans; Wezel, Jan Thomas van; Krzykalla, Julia; Benner, Axel; de Miranda, Noel F.; Knebel Doeberitz, Magnus von; et al. (Experimental and molecular pathology, 2021)
Lynch syndrome (LS) is caused by a pathogenic heterozygous germline variant in one of the DNA mismatch repair (MMR) genes: MLH1, MSH2, MSH6 or PMS2. LS-associated colorectal carcinomas (CRCs) are characterized by MMR deficiency and by accumulation of multiple insertions/deletions at coding microsatellites (cMS). MMR deficiency-induced variants at defined cMS loci have a driver function and promote tumorigenesis. Notably, PMS2 variant carriers face only a slightly increased risk of developing CRC. Here, we investigate whether this lower penetrance is also reflected by differences in molecular features and cMS variant patterns. Tumor DNA was extracted from formalin-fixed paraffin-embedded (FFPE) tissue cores or sections (n = 90). Tumors originated from genetically proven germline pathogenic MMR variant carriers (including 14 PMS2-deficient tumors). The mutational spectrum was analyzed using fluorescently labeled primers specific for 18 cMS previously described as mutational targets in MMR-deficient tumors. Immune cell infiltration was analyzed by immunohistochemical detection of T-cells on FFPE tissue sections. The cMS spectrum of PMS2-deficient CRCs did not show any significant differences from MLH1/MSH2-deficient CRCs. PMS2-deficient tumors, however, displayed lower CD3-positive T-cell infiltration compared to other MMR-deficient cancers (28.00 vs. 55.00 per 0.1 mm2, p = 0.0025). Our study demonstrates that the spectrum of potentially immunogenic cMS variants in CRCs from PMS2 gene variant carriers is similar to that observed in CRCs from other MMR gene variant carriers. Lower immune cell infiltration observed in PMS2-deficient CRCs could be the result of alternative mechanisms of immune evasion or immune cell exclusion, similar to those seen in MMR-proficient tumors.